Click Chemistry: A Revolutionary Tool in Drug Discovery and Development (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
“Click Chemistry” is a term which was first described by K. B. Sharpless in 2001 to chemical synthesis that is used to join two molecules. The application of the term, click, as a qualifier to the type of chemistry refers to an emphasis on efficiency and simplicity. To link two molecular components, each is first fitted with appropriate functional groups, such as azide and alkyne groups. These components are then “clicked” together in a process that is highly favorable and which tolerates many functional groups that might complicate other coupling processes. Among various click reactions, copper-catalyzed azide–alkyne cycloaddition (CuAAC) is the most widely studied due to its reliability and efficiency. In pharmaceutical industry, it helps scientists build large collections of test molecules quickly, attach medicines to targeted carriers, and create better treatments with high accuracy and very little waste. Main Uses in Medicine Production, drug discovery, target delivery , bioconjugation, better safety. click chemistry has become an important tool for developing innovative therapies and advanced drug delivery a systems.
Keywords: Click chemistry; CuAAC; drug targeting; drug discovery; bioconjugation; targeted drug delivery